Implementation of Budget Efficiency Policy in Realizing Good Governance at the Regional Secretariat of Bogor Regency - Surya Ahmad Maulani; Endeh Suhartini; Saprudin (International Journal of Science and Society, 2026)
This study aims to analyze the implementation of budget efficiency policies at the Regional Secretariat of Bogor Regency based on Presidential Instruction Number 1 of 2025 and Regent Circular Number 100.3.4.2/810-BPKAD. This research is significant as budget efficiency is the main part of efforts to realize good governance and a response to increasingly complex national fiscal challenges. A qualitative approach with a descriptive case study method was employed to gain an in-depth understanding of the processes, strategies, and challenges involved in implementing efficiency policies within the local government environment. Data were collected through in-depth interviews with key informants, direct observation of organizational activities, and review of relevant official documents. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, along with source and method triangulation to ensure the validity and reliability of findings. The results indicate that the policy implementation was formally carried out through budget adjustments, restrictions on operational expenditures, and postponement or cancellation of non-priority activities. However, structural challenges such as limited human and financial resources and cultural challenges such as resistance from some government officials were encountered. Key supporting factors for implementation included effective communication, leadership commitment, and inter-unit coordination. This study recommends that future efficiency policies adopt a more adaptive, participatory, and performance-based approach to enhance policy effectiveness and sustainability.